2014
DOI: 10.1186/1471-2474-15-167
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Open reduction and closed reduction internal fixation in treatment of femoral neck fractures: a meta-analysis

Abstract: BackgroundA meta-analysis was performed to assess the association between healing rate, avascular necrosis (AVN) of femoral head and two reductions-open reduction internal fixation (ORIF) and closed reduction internal fixation (CRIF) for femoral neck fracture.MethodsA literature-based search was conducted to identify all relevant studies published before September 10, 2013. The odd ratio (OR) and 95% confidence interval (CI) were used for estimating the effects of the two reduction methods. Data were independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…When necessary, open reduction could be performed. 16 Wang 17 conducted a meta-analysis, pooling the results to evaluate the correlation between ONFH and various reductions, open and closed, for femoral neck fractures. The results indicated there was a significant difference in terms of ONFH between the 2 reduction types.…”
Section: Discussionmentioning
confidence: 99%
“…When necessary, open reduction could be performed. 16 Wang 17 conducted a meta-analysis, pooling the results to evaluate the correlation between ONFH and various reductions, open and closed, for femoral neck fractures. The results indicated there was a significant difference in terms of ONFH between the 2 reduction types.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that for femoral neck fractures with signi cant displacement, the rate of necrosis was higher after open vs closed reduction but there was no difference in healing rate. [45] Use of stable-length implants…”
Section: Factors Contributing To Complicationsmentioning
confidence: 99%
“…For example, percutaneous cannulated screw fixation and closed reduction are effective in treating adolescents with femoral neck fractures, and minimal time from trauma to operation, rigid internal fixation, and good reduction can reduce the incidence of avascular necrosis and complications. Through comparing the treatment effects of closed reduction and open reduction for femoral neck fractures, closed reduction is found to have lower complication rates (including nonunion fracture healing and avascular necrosis). However, the results of different studies are not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…For femoral neck fractures, the therapeutic efficacies and postoperative complications of open reduction and internal fixation (ORIF) and closed reduction and internal fixation (CRIF) are similar and have no significant differences. A meta‐analysis by Wang et al (2014) evaluated the correlation between avascular necrosis and open/closed reduction for femoral neck fractures, revealing that CRIF leads to a higher avascular necrosis rate compared with ORIF. However, that meta‐analysis was not focused on femoral neck fractures in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%